The Effect of Direct and Indirect Corrective Feedback on Students' Writing Competency - Mahendra, P.I.K.S. (Universitas Pendidikan Ganesha, 2018)
The research objectives are 1) to prove the significant effects of direct and indirect corrective feedbacks on the students’ writing competency, 2) to prove significant differences of the effects of direct and indirect corrective feedbacks on the students’ competency in writing descriptive texts and recount texts. These research applied a quasi-experimental design with repeated measures. The sample was recruited from two intact classes using purposive sampling. Prior to conducting the experiment, the writing competency test was administered to measure the students’ writing competency across text types. Prior to administration, the instrument was validated for its readability (Readibility = 82.00), reliability (Cronbach alpha=0.98), and content validity (Pearson’s=1.00). The obtained data were analyzed descriptively and inferentially. The results show, firstly, there were significant effects of direct and indirect corrective feedbacks on the students’ writing competency at SMPN 2 Manggis. However, the effect of direct corrective feedback is more effective than that the indirect corrective feedback. Secondly, there were significant differences of the effects of direct and indirect corrective feedbacks across descriptive texts and recount texts especially on the descriptive text about place and recount text about students’ experience. However, the effect of direct corrective feedback is more effective than that the indirect corrective feedback. The results imply the necessity to apply the direct corrective feedback than the indirect corrective feedback when the Junior High School’s students write descriptive and recount texts